Migration Behaviour of Rural Youth in Haryana (Indian Journal of Extension Education, 2022)
Rural to urban migration has become an unavoidable event in the last 25 years with increased industrialization, growing service industry, better food security, access to improved healthcare and educational facilities in the cities apart from the rising ambitions of the youths. Agriculture always had a vital role in a village economy but this sector has not been financially rewarding in the past few decades and as a consequence of which, young generations from villages are leaving their family enterprises and migrating to cities for acquiring modern education and skills to secure a job in private sector. The study was conducted to find out the migration behaviour of rural youth in Bhiwani and Hisar districts of Haryana. A sample size of 192 rural youths i.e., 96 fully migrated & 96 partially migrated, were selected for the study. Findings revealed that unstable income, lesser employment, repeated crop failures were the push factors responsible for migration of rural youths. Higher wages, better jobs and better standard of livings in cities were the major pull factors motivating rural youths to migrate towards cities. Further, socio-economic & psychological variables such as age, education, farm size, non-farm skills, income expectancy, comfort expectancy, risk orientation, self-reliance & self-confidence had significantly positive correlation whereas, farm size, stimulation expectancy and affiliation expectancy had negatively significant relationship with migration behaviour of rural youth. Also, regression analysis showed that, seventeen independent variables selected for the study could explain 59.40 per cent variation in the migration behaviour of rural youths.